A Simpler Memristor Emulator Based on Varactor Diode. (May 2018) - Yu 于, Dong-Sheng 东升; Sun 孙, Ting-Ting 婷婷; Zheng 郑, Ci-Yan 辞晏; Iu, H. H. C.; Fernando, T.
Abstract : A new memristor (MR) emulator is designed by making use of only three current-feedback operational amplifiers, one varactor diode, one capacitor and five resistors. As compared with other reported MR emulators, only three active devices and ten components in total are required for realizing this MR emulator, and hence this emulator can be regarded as a simpler one for the moment. The results obtained by Multisim simulation and experimental prototypes are given to verify the practicality and feasibility of this MR emulator.